Isothermal phase transformation sequence in Fe-22wt%Cr-3.2wt%Mo-6.2wt%Ni-0.037wt%C cast duplex stainless steel - Kuimalee S. (2014)
Isothermal phase transformation behaviour in a Fe-22wt%Cr-3.2wt%Mo-6.2wt% Ni-0.037wt%C cast duplex stainless steel has been studied. The steel was solution heat-treated at 1175°C for 1 hour and isothermally heat-treated in the temperature range of 500-1,000°C for 8 to 32 hours, followed by water quenching. Microstructure characterisation was performed by scanning electron microscopy and electron probe microanalysis. The typical microstructure before heat treatment consists of primary austenite (γ1) and δ-ferrite. Four secondary phases were observed after transformation including carbide, chi (χ), sigma (σ) and secondary austenite (γ2). These phases can be distinguished by the bright contrast level in backscattered electron images in the order of χ > σ > γ1 or γ2 > δ > carbide. The transition temperature range where the σ phase took precedence over the χ phase as a major transformation product is approximately above 700°C. Features of the isothermal phase transformation sequence of the cast material are discussed in comparison to that of wrought duplex stainless steel.